The two most common swimming faults, part 1 - Woolley, H.
This article will teach you important fundamentals of swimming technique and change the way you think about swimming forever. The two common faults in swimming revolve around two commonly discussed concepts in swimming, that of 1. correct body position and 2. shouldewr extension In this article the first of these two concepts will be discussed in greater detail.